2017
DOI: 10.1080/21645515.2016.1256519
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pneumococcal disease: From a tertiary care hospital in the post-vaccine era

Abstract: A breakthrough infection occurring with 13-valent pneumococcal conjugate vaccine (PCV13) in Turkey are previously described. A breakthrough infection is defined as IPD in a child who had received 1 PCV-7 or PCV-13 and for which the pneumococcal isolate was a vaccine serotype. During one year period, among 6 patients with invasive pneumococcal infection, 2 patients were considered to have a vaccine failure with serotype 19F. Antibiotic resistance results were remarkable; macrolide resistance were observed in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…19 In the literature, several cases were reported of those who had IPD due to PCV13 serotypes despite having received at least two doses of PCV vaccination. [20][21][22][23][24][25][26][27][28] There is a lack of information about the risk of IPD with vaccine-types after completing the recommended course of PCV immunization. After the vaccination, the changes of antibody titers against serotypes affect the serotype distribution of IPD besides the serotype carriage.…”
Section: Discussionmentioning
confidence: 99%
“…19 In the literature, several cases were reported of those who had IPD due to PCV13 serotypes despite having received at least two doses of PCV vaccination. [20][21][22][23][24][25][26][27][28] There is a lack of information about the risk of IPD with vaccine-types after completing the recommended course of PCV immunization. After the vaccination, the changes of antibody titers against serotypes affect the serotype distribution of IPD besides the serotype carriage.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance causes different clinical presentation of disease, making it more difficult to diagnose and to treat. 11 12 The patient's clinic and laboratory features were not compatible with IRAK-4 or MyD88 deficiencies. According to our knowledge, a case of PNP in a child fully immunized has not been reported in literature.…”
Section: Discussionmentioning
confidence: 95%
“…18 There are cases of infection reported despite vaccination. Basaranoglu et al 19 reported infection with 19 F strains despite vaccination in two patients. Both patients had underlying neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…One of the patients had a pneumonia infection, and the other had meningitis. 19 Park et al 20 found an infection rate of 21% despite vaccination. The serotypes most commonly causing infection were 6B and 19F.…”
Section: Discussionmentioning
confidence: 99%